2021
DOI: 10.1016/j.redox.2021.102141
|View full text |Cite
|
Sign up to set email alerts
|

Deacetylation-dependent regulation of PARP1 by SIRT2 dictates ubiquitination of PARP1 in oxidative stress-induced vascular injury

Abstract: Poly(ADP-ribose) polymerase 1 (PARP1) has a major regulatory role in cardiovascular disease. However, inhibiting PARP1 activity does not significantly improve clinical outcomes of cardiovascular disease, which suggests that the regulatory mechanism of PARP1 in cardiovascular disease is unclear. Here, we focused on deacetylation regulatory mechanisms of PARP1 and crosstalk of PARP1 post-translational modifications. We uncovered the crucial molecular interactions and protein modifications of deacetylase Sirtuin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 26 publications
2
19
0
Order By: Relevance
“…These findings suggest that the mechanism by which probiotics alleviate vascular endothelial dysfunction may be related to the inhibition of oxidative stress. Oxidative stress is a crucial factor leading to endothelial dysfunction, including direct damage to the vascular endothelium, induction of inflammation, and oxidation of LDL-C, inhibition of excessive oxidative stress response in vascular endothelium has been proven effective in counteracting the progression of AS [59][60][61]. Some probiotics have been shown to exhibit superior antioxidant capacity.…”
Section: Probiotics Improve Endothelial Dysfunctionmentioning
confidence: 99%
“…These findings suggest that the mechanism by which probiotics alleviate vascular endothelial dysfunction may be related to the inhibition of oxidative stress. Oxidative stress is a crucial factor leading to endothelial dysfunction, including direct damage to the vascular endothelium, induction of inflammation, and oxidation of LDL-C, inhibition of excessive oxidative stress response in vascular endothelium has been proven effective in counteracting the progression of AS [59][60][61]. Some probiotics have been shown to exhibit superior antioxidant capacity.…”
Section: Probiotics Improve Endothelial Dysfunctionmentioning
confidence: 99%
“…Studies have shown that SIRT2 can also deacetylate PARP1 K249, resulting in the ubiquitination and degradation of PARP1 by WW domain-containing protein 2 (WWP2), thereby alleviating the vascular oxidative stress injury caused by PARP1 mediated by angiotensin II (Ang II) [ 107 ]. Alternatively, SIRT2 can deacetylate K431 of Bcl-2-associated athanogene 3 (BAG3), thereby mediating BAG3 binding to PARP1 to promote the ubiquitination degradation of WWP2 at PARP1 K249 to protect against oxidative damage [ 108 ].…”
Section: Sirt2 and Metabolic Disordersmentioning
confidence: 99%
“…Studies have shown that during atherosclerosis, SIRT2 can inhibit the occurrence and development of atherosclerotic macrophages by inhibiting the polarization of macrophages [ 139 ]. Alternatively, SIRT2 can directly act on its target Nrf2/FOXO3/PARP1 and indirectly act on PARP1 by deacetylating BAG3, which alleviates the further aggravation of hypertension and oxidative stress, prevents intraluminal occlusion and stenosis from causing organic lesions, and avoids the occurrence of coronary heart disease (CHD) of myocardial ischaemia [ 97 , 98 , 107 , 108 ]. Furthermore, in acute myocardial infarction (AMI), functional DNA sequence variants (DSVs) can alter the SIRT2 levels by affecting the transcriptional activity of the SIRT2 promoter, leading to the progression of AMI into severe disease [ 140 ].…”
Section: Role Of Sirt2 In Diseasementioning
confidence: 99%
“…Therefore, in the vascular milieu of low-grade sterile inflammation, the defense mechanism of sirtuins will be impaired. In particular, sirtuin 2 has been shown to protect against oxidative stress-induced vascular injury by deacetylation and ubiquitination of the oxidative stress injury-related protein poly(ADP-ribose) polymerase 1 (PARP1) in mice [ 64 ]. Besides, one of the mechanisms by which sirtuins mitigate chronic inflammation in the vasculature is the inhibition of the NLRP3 inflammasome [ 65 ].…”
Section: Oxidative Stress and The Nlrp3 Inflammasomementioning
confidence: 99%